m-3+13=20

Simple and best practice solution for m-3+13=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m-3+13=20 equation:


Simplifying
m + -3 + 13 = 20

Reorder the terms:
-3 + 13 + m = 20

Combine like terms: -3 + 13 = 10
10 + m = 20

Solving
10 + m = 20

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + m = 20 + -10

Combine like terms: 10 + -10 = 0
0 + m = 20 + -10
m = 20 + -10

Combine like terms: 20 + -10 = 10
m = 10

Simplifying
m = 10

See similar equations:

| 2x-3=2x+2 | | 5n^2-40n=0 | | g+48=54 | | 6y+6=2y+8 | | 9-4x=2x-3 | | 45/4m=35/3 | | f=53-24 | | 5k^2+20k=-15 | | ln(x)+ln(2x)=0 | | 52y-3.1=12 | | 19(v+4)-3v=4(4v+4)-24 | | 5x6/15-2 | | 2-x=2x-6 | | 3m^2-6m=9 | | 4.5(x+5.5)=4.5(x+5.5) | | 13t+10=-3 | | 5t+6=26 | | x^3=6x+x^2 | | 26+3y-3=15y-12-5y | | 5a-10=-5a | | 6v^2+252=78v | | 12y+164=7.6 | | 50t^2+80t+32= | | 0.18y+0.02(y+6000)=1120 | | 1-3/5=-1/5 | | -3(-2)+4= | | 5m^2-18M+9=0 | | -5/2t=4 | | -19(-2)= | | 6c-a/7=b | | 9m+3m-10=3(3m+3) | | 10=4k+6 |

Equations solver categories